PARENTING APPROACHES: ENHANCING PRE-LITERACY AND NUMERACY SKILLS IN EARLY CHILDHOOD - Wati, Rina; Sobri, Ahmad Yusuf; Pramono, Pramono (Jurnal Konseling Pendidikan Islam, 2025)
This study will analyse how parenting programs improve pre-literacy and numeracy skills in early childhood. This study uses a case study approach, where interviews, observations and documentation are used as media for data collection. Data are analysed in stages, from data display, data reduction, and concluding with conclusion drawing. The results of the study show that parenting programs in improving pre-literacy and numeracy skills in early childhood are carried out through providing stimulation through daily activities, building a supportive learning environment, an individualised approach in learning, and increasing family involvement in children's education. This study offers implications for the importance of parenting programs in pre-literacy and numeracy skills in early childhood through daily stimulation, a supportive learning environment, an individualised approach, and family involvement. These findings provide insight into developing more structured and relevant parenting programs to support optimal child development at home and school.